Espacio público para todos: using purpose-oriented amenities to enhance childhood development in Mexican public spaces - Ewald, Lauren (Kansas State University, 2013)
The issues infested in urban slum communities are many, of which I had no problem indentifying a dilemma specific to my interests in landscape architecture and socially equitable places. However, sustainable solutions specific to these dynamic urban forms and communities are unfamiliar academic territory. Extreme levels of poverty fostered in these communities cause deficiencies in a child’s development, who are often without access to a formal, structured education system (UNDP, 1999). Public spaces are particularly stimulating environments for youth learning and development, but most urban environments in shanty towns host a milieu of violence and crime, making most public streets and vacant lots unsafe. These conditions are ripe for visionary designers to intervene, improving the physical aspects of urban public spaces and specifically bettering the quality of life for children living in these communities. Answering this question required literature research and precedent studies, which was important for developing a thorough understanding of developmental theory as it relates to socio-economically disadvantaged children. By focusing my studies on public spaces in the neighborhood Vistas del Cerro Grande in Chihuahua, México, I began to understand the cultural idiosyncrasies specific to people living in urban shantytowns. Data collected from the neighborhood via surveys, interviews, community meetings, and an auto-ethnographic video study with fifth and sixth grade students provided an introduction to the community and the larger themes and objectives for future public space design. Visiting comparable communities in México City, México deepened my understanding as I was able to observe the daily lives of México City residents with diverse socio-economic statuses, hear their individual perspectives on the history and cultures, and relate to their frustrations with current political, economic, and societal systems. The methodologies described above culminated in a design typology specific to Vistas del Cerro Grande, consisting of public streets, pedestrian access ways, plazas, and vacant lots. These types form the backbone of my research report, which represents an evidence-based design palette of purpose-oriented amenities for positive childhood development in shanty town public spaces. The typology caters to the specific needs of the Vistas del Cerro Grande community, as identified in the research.
Keywords: Chihuahua, Mexico; Child development; Auto-ethnography; Public space design; Rapid urbanization; Sustainable community amenities; Cultural Anthropology (0326); Developmental Psychology (0620); Landscape Architecture (0390)